VULVA HYGIENE BEHAVIOR DETERMINED BY HEALTH LITERACY AMONG ADOLESCENT GIRLS - Wijaya, Yosi Maria; Maria Regina Hesti Sintiasari; Lidwina Triastuti (Universitas Airlangga, 2025)
Introduction: Teens as young as 15-24 are vulnerable to reproductive system infections due to poor teenage vulva hygiene, exacerbated by a lack of understanding of the vulva's functioning. According to estimates, teenagers worldwide report reproductive channel infections. Previous research revealed that 46% of teenagers had poor reading skills. Aim: The goal of this study is to assess the association between healthy habits and vulva cleanliness in teenage girls. Methods: The study employs quantitative approaches, with 289 responses from high school students obtained by proportionally organized random sample processes. The HLS-EU-16Q Indonesian instruments and the vulva hygiene behavior scale have been approved as reliable. Results: This study discovered a significant relationship between health literacy and vulva hygiene practices (p-value= 0.05). Furthermore, 46% of the subjects have adequate health literacy, whereas 58.8% practice intermediate vulva hygiene activities. Conclusion: Proper health literacy can impact how teenage girls clean up their vulva. Researchers propose that young women can improve their vulva hygiene by seeking information, undergoing therapy, and consulting with health care providers.